2014
DOI: 10.9756/bijiems.10350
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study: A Process FMEA Tool to Enhance Quality and Efficiency of Manufacturing Industry

Abstract: Abstract---

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…Risk Priority Number can figure out the seriousness of potential risk indicated the larger RPN values. If the RPN is identical, the Severity (S) multiply by Occurrence (O) = S x O should be considered because the occurrence plays more role after the severity in risk management [11]. 2) Project Risk Management Project risk management is part of the Project Management Book of Knowledge (PMBOK) which are generally accepted as the greatest practice within project management [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk Priority Number can figure out the seriousness of potential risk indicated the larger RPN values. If the RPN is identical, the Severity (S) multiply by Occurrence (O) = S x O should be considered because the occurrence plays more role after the severity in risk management [11]. 2) Project Risk Management Project risk management is part of the Project Management Book of Knowledge (PMBOK) which are generally accepted as the greatest practice within project management [13].…”
Section: Methodsmentioning
confidence: 99%
“…FMEA is also studied by Tejaskumar S.Parsana dan Mihi T. Patel to improve the quality and efficiency of Manufacturing Industry. The prevention action also proposed according to risk prioritization [26].…”
Section: Related Workmentioning
confidence: 99%
“…The higher number RPN represents a higher risk of defects. [6] For the analysis of the various failure modes and their potential consequences could be applied Ishikawa diagram also called as Fishbone diagram. This diagram is simple graphic method for root cause analysis of any problems.…”
Section: Rpn Severity Occurence Detectionmentioning
confidence: 99%
“…Several studies have shown that FMEA is a fairly effective technique for assessing risk [25]. For example, it has been employed in studies on supply chain risk management [26], analysis and problems on small-scale textile business [27], waste risk measurement [28], and new product development [29]. Other studies on FMEA have been carried out related to the improvement of the quality and efficiency of manufacturing [30].…”
Section: Introductionmentioning
confidence: 99%